Eksplorasi Dan Identifi kasi Anggrek Terestrial Di Kawasan Gunung Jambu Jalur Pendakian Arah Lembang Kecamatan Tanjungsari Kabupaten Sumedang - Iis Aisyah; Rosidah Rosidah; Agus Surya Mulya (Paspalum: Jurnal Ilmiah Pertanian, 2023)
Orchid is one of the ornamental plants that has a relatively high selling power and attractiveness, there are several types of orchids, including terrestrial orchids, this orchid is one of the orchids that grows and develops on the soil surface. its presence in the forest component and grows wildly, so if the forest component is disturbed it can threaten the sustainability of terrestrial orchids. Exploration and is one of the first steps in the existence of terrestrial orchids. This study aims to obtain data, study and obtain types of terrestrial orchids and vegetation in the Mount Jambu Area, Climbing Route to Lembang, Tanjungsari District, Sumedang Regency. This experiment was carried out from June to July 2021. The method used in this study was exploratory which was analyzed by descriptive method. The results of the study found 11 species, the orchid Nervilia punctata (BI.) Lindl., and Cymbidium lancifolium Hook. is an orchid that dominates in the Mount Jambu area of the hiking trail to Lembang and the vegetation in the area is a type of herbaceous plant that has narrow leaves and grows wild.